A Forest Protection Model Based on Local Wisdom of the Kotabaru Dayak Indigenous Communities in Kalimantan Selatan Forest Conservation - Mahyuni, Mahyuni; Topan, Muhammad (Scholar Center, 2023)
Indonesia's forest management is still unable to fulfill the constitutional mandate, thus driving the rate of forest degradation and deforestation. This very high damage occurred in the concession area, therefore forest management in customary lands must be returned to indigenous peoples who do have constitutional rights. Furthermore, based on previous research conducted by the World Resource Institute, forest management under the control of indigenous peoples runs more effectively than forest management outside the scope of adat and can reduce the rate of forest deforestation. The purpose of this research is to answer 2 (two) main issues, namely; (1) Analyzing forest protection based on local laws of the Dayak Kotabaru indigenous people on environmental sustainability; (2) Finding a forest protection model based on the local law of the Dayak Kotabaru indigenous people in Kalimantan Selatan. The research method used in the first year is an empirical research method that examines the forest protection model based on local laws of the indigenous Dayak community in Kalimantan Selatan. In the second year, using the socio-legal research, discovered the concept of regional policies in forest management based on the values ??contained in the local legal system of the Dayak indigenous people in Kalimantan Selatan.